Incontro Fuori Luogo. Interview with Salvatore Monaco - Urciuoli, Carmine (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2019)
Salvatore Monaco - PhD in Social Sciences and Statistics with the thesis “The future of tourism. Between traditional paths and new mobility ". He is one of the youngest Italian researchers dealing with Sociology of Tourism. For several years he has collaborated with the LGBT Observatory and with OUT - University Observatory on Tourism of the "Federico II". His research proposes mobility as an interpretative key of social reality and focuses, in particular, on issues related to social exclusion, urban contexts and the use of technologies and new media, with specific attention to issues related to identities, genders, sexual orientations and generations. On these topics he has published several articles, including in international journals. Among the most recent "Sport and Tourism in Contemporary Society" (with R. Blanco Gregory, 2019), "Tourism and the New Generations: Emerging Trends and Social implications in Italy" (2018), "Cosmetic Tourism: Bodies and Identities Between New Opportunities and Unseen Risks "(with F. Corbisiero, 2017).